Application of phosphate solubilizing bacteria on different type of soil towards availability of phosphorus / Nur Faraha Umar - Umar, Nur Faraha (Faculty of Plantation and Agrotechnology, 2016)
A study was conducted to identify the availability of P through application of Phosphate Solubilizing Bacteria (PSB) on different types of soils which are peat soil, acid sulphate soil, BRIS soil and soil mixture as control treatment. The different types of soil were inoculated with bacterial strains, Bacillus safensis and were planted with aerobic paddy as crop indicator. Analysis on soil pH, total P and available P in soil were carried out. The growth performance of paddy such as plant height was recorded weekly whereas the root length and plant biomass were collected at week six. Research showed that the aerobic paddy planted in peat soil and acid sulphate soils were significantly increased in plant height compared to other treatments. The root length and plant biomass grow on peat soil show the highest value compared to other soils. After application of PSB, all treatments showed an increase of soil pH except for BRIS soil which the soil pH were significantly decreased. Before the application of PSB, the total P in all treatments was high especially with soil mixture and peat soil. However after the application of PSB, total P in all soils was significantly decreased due to conversion the P to available P. BRIS soil has the lowest total P and available P.